Dialektika Agama dan Budaya: Tradisi Kenduri Sebagai Ekspresi Religius Desa Sukorejo Kemiri - Alifa Nurul Mufiroh; Asy Sifa Patricia Pratama; Muthi’ Fauziyah; Vava Imam Agus Faisal (Islah Tarbawi: Journal of Islamic Education and Learning, 2025)
This study is motivated by the strong persistence of the kenduri practice in Sukorejo Kemiri Village, which reflects an ongoing dialectical process between Islamic values and local cultural traditions. The research focuses on analyzing the forms of kenduri implementation, its religious meanings, and the patterns of interaction between Islamic teachings and local cultural practices. This study employs a qualitative method with a phenomenological approach through in-depth interviews, observation, and documentation, followed by data reduction, data presentation, and conclusion drawing. The findings reveal that kenduri carries significant spiritual, social, educational, and economic functions within the community. Spiritually, the ritual serves as a medium for collective prayer, tahlil, and expressions of gratitude to Allah. Socially, it strengthens communal solidarity and maintains harmonious relationships among residents. Educationally, it transmits values of charity, gratitude, cooperation, and social responsibility. Economically, kenduri stimulates local economic activities through food preparation, service exchanges, and community-based contributions. The study identifies two patterns of dialectics: the theological–compromising pattern, in which Islamic values refine traditional practices to align with religious norms; and the theological–humanistic pattern, in which Islamic teachings reinforce social cohesion and communal ethics. The study concludes that kenduri remains sustainable because it successfully integrates religious values with local cultural identity in a harmonious and adaptive manner.